Female Main Character in Princess Mononoke Film: A Study of Ecological Feminism - Sanjigandewi, Ni Putu Rhadani; Setianingsih, Ni Ketut Alit Ida (Humanis; Vol 26 No 1 (2022)DO - 10.24843/JH.2022.v26.i01.p02, 2022)
This study aims to analyses the female main character in Princess Mononoke film that reflects ecological feminism. The data of this study was taken from the Princess Mononoke film. The data were analyzed by using the narrative-qualitative method. Theory of women-other human Others-nature interconnections by Karen J. Warren (2000) was applied to find out the connection of the female main character with nature. The results of this study show that the oppression of the forest leads to the oppression of the female main character. The forest was destroyed by humans, which lead to the oppression of Princess Mononoke because she lost her family, friend, and home.